The role of internet of things (IoT) in biomedical engineering : present scenario and challenges /: present scenario and challenges. (2021) - Priyadarshini, Sushree Bibhuprada B; Sharma, Devendra Kumar; (Assistant professor of electronics), Sharma, Rohit; Cengiz, Korhan
No abstract available